The first person pronominal subject in magazines of Turma da Mônica: a short-term real-time analysis (PERcursos Linguísticos, 2022)
In the present study, it was observed, through a short-term real-time analysis, the variation of the first-person pronominal subject's expression in Turma da Mônica magazines in three different synchrony: 1970s, 1990s and 2010s. In Brazilian Portuguese (PB), this variable can appear in two forms: filled (“Como eu gostaria que a humanidade perdesse o olfato”) and null (“ø Vamos voltar pro céu!”). As theoretical basis, Variationist Sociolinguistics (LABOV, 2008 [1972]) and the works of Duarte (1993 [2018]) and Silva (2004) were used, which bring different results to the phenomenon. The results show a stagnation in the change of the pronominal subject, which remains above 50% in the three synchronies: 66.5% in 1970; 52.8% in 1990 and 54.2% in 2010, which proves that the PB still has a partial pro-drop parameter.